1994
DOI: 10.1093/jac/33.4.737
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sparfloxacin on Staphylococcus aureus adhesiveness and phagocytosis

Abstract: We investigated the effect of sparfloxacin, a new broad-spectrum fluoroquinolone, on the morphology, adhesiveness and phagocytosis of a clinical isolate of Staphylococcus aureus sensitive to this compound (MIC = 0.06 mg/L). The strain was tested for its adherence to human buccal epithelial cells, measured by interference contrast microscopy, and for phagocytosis by guinea-pig peritoneal macrophages, measured by fluorescence microscopy. Accumulation of sparfloxacin by macrophages was studied by means of a veloc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
3
0

Year Published

1998
1998
2002
2002

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 12 publications
3
3
0
Order By: Relevance
“…Similar observations were made for ciprofloxacin in mouse and human phagocytes (10,11). A much higher value was reported for sparfloxacin by using guinea pig peritoneal macrophages (8). As was observed with other quinolones (8,12,13,(27)(28)(29), we also found that 80 to 90% of the intracellular enrofloxacin was released from phagocytes within 10 min when the phagocytes were placed in enrofloxacin-free medium.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Similar observations were made for ciprofloxacin in mouse and human phagocytes (10,11). A much higher value was reported for sparfloxacin by using guinea pig peritoneal macrophages (8). As was observed with other quinolones (8,12,13,(27)(28)(29), we also found that 80 to 90% of the intracellular enrofloxacin was released from phagocytes within 10 min when the phagocytes were placed in enrofloxacin-free medium.…”
Section: Resultssupporting
confidence: 89%
“…In the latter case, phagocytosis by AMs and PMNs was independent of the serum concentration. Under all variations of serum concentration and particle type, no significant differences in phagocytosis by PMNs or AMs were observed in the presence or absence of enrofloxacin (P Ͼ 0.570), as was described by others (8,12,23) for other quinolones. As is evident from Fig.…”
Section: Resultssupporting
confidence: 70%
“…In fact, surfactant phospholipids have been shown to exert suppressive effects on immune cell functions including cytokine release, lymphocyte proliferation, immunoglobulin production and natural killer cell cytotoxicity [4,5,7].A limited number of investigators have examined the effect of subinhibitory concentrations of antibiotics on the adherence of respiratory pathogens to epithelial cells [9,12,13,15,19]. Moreover, there are only few reports on the influence of pulmonary surfactant on antibiotic activity [20][21][22].…”
Section: Discussionmentioning
confidence: 99%
“…Pulmonary surfactant is a complex mixture of lipids (mainly phospholipids), proteins and carbohydrates which lines the alveolar surface of the lung and reduces the surface tension at the air-liquid interface [3,4]. Another wellcharacterized function of this complex is its involvement in the defense system of the lung, mainly attributable to surfactant protein-A (SP-A), a surfactant protein that, thanks to its opsonizing activity, favors nonspecific clearance of microorganisms by phagocytic cells [3][4][5][6][7].At subinhibitory concentrations, some antibiotics can prevent the formation of adhesins or affect their structure and functional properties, thus preventing the adherence of respiratory pathogens to the host cells [8][9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…By exposing a Staphylococcus aureus strain isolated from a bronchial aspirate to subinhibitory concentrations of sparftoxacin, DESNOTTES and DIALLO (1994) demonstrated that 1/2 and 1/4 of the MIC reduced the adherence by more than 50%; 1/8 and 1/16 of the MIC reduced it to 40% and 20%, respectively. No differences to the drug free controls were detectable at 1/32 of the MIC.…”
Section: B Effect On Adherencementioning
confidence: 99%